REKONSTRUKSI PEMAHAMAN KESETARAAN GENDER DALAM AL-QUR'AN MELALUI ANALISIS KONTEKSTUAL AYAT-AYAT GENDER - A.Izzul Haq; Hasyim Haddade; Rosmini Rosmini (Journal of Innovative and Creativity (Joecy), 2026)
Gender equality in Islam remains a significant issue in contemporary Islamic discourse, as different interpretations of Qur’anic verses often generate diverse perspectives on the roles and positions of men and women in social life. This article aims to analyze the concept of gender equality from the Qur’anic perspective, examine the contextual interpretation of gender-related verses, and explain their relevance to contemporary Muslim society. This study employs a library research method using a thematic (maudhu’i) exegesis approach and descriptive qualitative analysis. The data were collected from the Qur’an, classical and contemporary Qur’anic commentaries, and relevant scholarly literature. The findings reveal that the Qur’an positions men and women as human beings who possess equal dignity, moral responsibility, and opportunities to attain honor before Allah. A contextual interpretation of gender-related verses demonstrates that several provisions commonly perceived as reflecting inequality are, in fact, closely linked to the socio-historical circumstances of the revelation and are intended to promote justice and public welfare (maṣlaḥah). Therefore, gender equality in Islam represents a manifestation of the Qur’anic values of justice and continues to serve as an ethical foundation for fostering harmonious social relations in contemporary society.